Pertumbuhan dan Hasil Tanaman Pegagan pada Aplikasi Jenis Pupuk Organik - Refa Firgiyanto; Vera Elfina; Tri Rini Kusparwanti; Gallyndra Fatkhu Dinata; Fadil Rohman; Rindha Rentina Darah Pertami (Jurnal Ilmu Pertanian Indonesia, 2023)
Gotu kola is one of the medicinal plants that is widely used because of its various nutritional content. In general, the cultivation only uses inorganic fertilizers, which have long-term effects that are not good for the environment. The use of organic fertilizers is an effort to produce high-standard products. Rabbit urine liquid organic fertilizer and goat manure are alternative types of fertilizer that can be given. Therefore, this study aimed to determine the response of giving liquid organic fertilizer of rabbit urine and goat manure and their interaction with the growth and yield. The study used a Factorial Randomized Block Design (RBD). The first factor was rabbit urine liquid organic fertilizer (LOF) with a concentration of 0, 2, and 4%. The second factor was goat manure with doses of 0, 37, and 75 g/polybag. The results showed that applying rabbit urine (LOF) and goat manure increased the growth and yield of gotu kola. Application of 2% rabbit urine LOF significantly increased stalk length compared to controls. Gotu kola plants given 37 g/polybag of goat manure produced stolons that were significantly longer than those treated with goat manure 75 g/polybag and had significantly heavier roots than other treatments. The interaction of rabbit urine LOF and goat manure application had no significant effect on all observed variables. Keywords: goat manure, gotu kola, liquid organic fertilizer, rabbit urine